LI-FI Performance Analysis in Various Aquatic Environments for Reliable Underwater Communication - Hemanth T M; Manjunath K M; Suhas Gowda H B; Vrunda Kusanur; Jyoti R Munavalli (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
The ability to communicate reliably and quickly underwater has been one of the driving forces behind the development of alternative technologies to conventional radio frequency systems. This study explores the performance of Light Fidelity (Li-Fi), a high-speed optical wireless communication technology, in diverse aquatic environments like fresh water, salt water, and turbid water. It evaluates key parameters like signal attenuation, data rate, bit error rate, and transmission range. Results show that Li-Fi offers significant advantages in bandwidth and data rate over traditional methods, but its efficiency is highly dependent on environmental conditions. The study recommends optimizing Li-Fi systems for reliable underwater communication, paving the way for enhanced underwater networking and data transmission applications.